The Manageable Development is a Lean Basis for a Small Organization - Baksi, Zsolt (International Journal of Engineering and Management Sciences, 2018)
The lean approach is based on the buyer, while eliminating losses, in addition to value creation and efficiency gains, it determines the direction of developments in the process. To successfully build and maintain lean, engagement and development is indispensable, but it is not as simple as changing past behaviors and attitudes. The company also realized that changes were needed, as the increased number of employees in the company, and the increase in production and the profits associated with it, made it clear that organizational development is needed. The organization development was started by SWOT analysis, and along with Ishikawa's assay, I discovered whether LEAN was necessary for the company. With Gemba, I took a look at the problems and then categorized them to designate development points.